Raising awareness of chronic kidney disease in a Brazilian urban population - Mazza Nascimento,M. (2009)
The incidence and prevalence of chronic kidney disease have been increasing in recent years in developing countries. The aim of this study was to report the results of a general chronic kidney disease awareness program applied to an urban population in a large Brazilian city. From January 2002 to January 2005 a total of 8883 individuals in the city of Curitiba (PR, Brazil) were screened for hypertension, body mass index, hematuria, and proteinuria. A family history and previous medical diagnosis of hypertension and diabetes mellitus (DM) were also recorded. Of the 8883 individuals assessed, 56% were women, subject median age was 47 years (range: 17-93 years) and more than 90% were Caucasian. Thirty percent had signs of hematuria, 6% had proteinuria, and 3% had hematuria and proteinuria. The median of mean arterial pressure values was 93 mmHg (range: 71-135 mmHg) and 16% of the population screened had a history of hypertension. A significant positive family history of both hypertension or DM was present in 42% (P < 0.0001; chi-square = 83.18) and 7% (P < 0.0001; chi-square = 161.31) of the hypertensive group, respectively. Finally, the prevalence of hypertension and DM was significantly higher in older individuals with proteinuria. In the present study, a higher prevalence of hematuria and proteinuria was found in older individuals with hypertension and diabetes compared to the general population. These data confirm the need for public awareness of renal disease in high-risk individuals.